Development of professional competence of motor transport engineers in the system of postgraduate pedagogical education - Hornostaieva, О. (Problems of Engineer-Pedagogical Education, 2019)
The article discusses the development of professional competence of motor transport engineers in the system of postgraduate pedagogical education. Today, the improvement of the pedagogical skills of teachers is of particular importance in the higher education system. The basis of the teacher‘s pedagogical skills is pedagogical competence. The need to improve the skills of engineers-teachers results from changes in the external and internal environment, improvement of the management process, development of new types and fields of activity. Advanced training of engineers-teachers is aimed at improving and deepening their knowledge and skills in a profession or a received specialty in accordance with the requirements of the production or services sector on the example of the motor transport sphere. The paper substantiates that the process of advanced training compensates for the shortcomings of basic pedagogical or technical training of engineers-teachers, helps them adapt to the results of the development of the latest achievements in science and technology, master modern technologies, knowledge, and also improve their methodological level. The analysis of the development of the system, which is postgraduate pedagogical education, aimed at solving the problems of training and raising the level of skills of teaching staff, has been carried out. It has been established that in the process of advanced training the necessary prerequisites are provided for the formation and development of the engineer-teacher‘s competence, which is an important component of the concept of lifelong learning. The article reveals that the advanced training system is quite a powerful and effective tool that is able to contribute to the professional development of the engineer-teacher, and accordingly to ensure the dynamic organizational development of the educational sphere. Based on the analysis of scientific sources, it has been found that engineering-pedagogical education is not a mechanical combination of two types of education, but a qualitatively new type of knowledge, which is characterized by the interpenetration of one industry into another, the close and rational integration of psychological, educational, engineering and production technological components in the training of specialists